2005
DOI: 10.3769/radioisotopes.54.315
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of 222Rn Concentrations in Surface Water in Northeast Thailand

Abstract: In northeast Thailand, salinization caused by the discharge of salty groundwater is a serious problem. Locations where groundwater flows into surface water must be identified before measures against saliniza tion can be taken. Radon-222 (222Rn) is a useful indicator for determining areas of groundwater discharge. We measured 222Rn concentrations in surface waters in the region and found that groundwater flows into streams and lakes in low-elevation areas (below 180m). Our results agree with the results of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Higher radon concentration during the post-storm event could be the result of increased groundwater influx from the shallow aquifer into the river basin [34]. Rapid increase of groundwater table during the storm period could increase the hydrostatic pressure thus increase the lateral groundwater discharge into adjacent river [31,32]. Level of radon recorded during post-storm was at least one magnitude higher compared to the dry period, indicates high portion of groundwater contributing to storm flow generated in Ular River.…”
Section: Resultsmentioning
confidence: 99%
“…Higher radon concentration during the post-storm event could be the result of increased groundwater influx from the shallow aquifer into the river basin [34]. Rapid increase of groundwater table during the storm period could increase the hydrostatic pressure thus increase the lateral groundwater discharge into adjacent river [31,32]. Level of radon recorded during post-storm was at least one magnitude higher compared to the dry period, indicates high portion of groundwater contributing to storm flow generated in Ular River.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been reported that the 222 Rn concentration at location 3, which is a small stream, was higher in the rainy season than in the dry season because of greater subsurface flow in the rainy season 8 . However, the 222 Rn concentration (Table 1) and the electric conductivity (Table 2) at the end of August (August 29-31) were very low, at 11 mBq/L and 51 µS/cm respectively.…”
Section: Influence Of Human Activity On 222 Rn Concentration In Surfamentioning
confidence: 99%